Development of a Combination of Passing and Dribbling Training Model in Football Games at SSB Rajawali Muda FC U-13 (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this study was to develop a combination of passing and dribbling training model that is applicable and able to improve the basic skills of U-13 players at SSB Rajawali Muda FC. The research method used in this study is Research and Development (R&D) by adapting the stages of the Borg & Gall development model. This study involved 24 players from the Rajawali Muda FC Football School (SSB) in the under-13 age category (U-13) as research subjects. Product validation was carried out by five experts using Aiken's V technique to measure validity, while the reliability test used the Intraclass Correlation Coefficient (ICC) method. The results of the study showed that the combination of passing and dribbling training model developed was considered very feasible by the experts, in terms of the content of the material, the sequence of exercises, the use of tools, the clarity of instructions, and the duration of implementation. The results of the validity test using Aiken's V formula obtained a value of 0.91, while the inter-rater reliability test using the Intraclass Correlation Coefficient (ICC) method showed a value of 0.946, which indicates a very high level of reliability. In addition, the results of the field trial proved that there was a significant increase in the passing and dribbling abilities of players after following this training model, which was supported by the results of the Paired Sample T-Test with a significance value of 0.001. This study concludes that it has succeeded in developing an effective and applicable combination of passing and dribbling training model for U-13 players. This model improves basic skills, teamwork, and coordination, so it can be used as a reference for coaches in coaching early age football in a fun and structured way.